“Tristezza Siderurgica” - Pisapia, Jasmine (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2022)
This essay emerges from conversations between an anthropologist and a performance artist from the industrial city of Taranto, in southern Italy—known today to be one of Europe’s most polluted cities due to the continent’s largest and most hazardous steel factory. By focusing on artist Isabella Mongelli’s photographic and theatrical work conducted upon returning to her hometown after years lived abroad, this essay locates the expression of a specific affect coined by Taranto sound artist Alessandra Eramo: la tristezza siderurgica, the sorrow of steel. Tristezza siderurgica yields an ethnographic understanding of the perceptions and representations of homes that have become homely, uncanny, estranged because toxic or otherwise inhospitable. The article shows that the naming of affects contributes to forging specific, perhaps even untranslatable, emotional landscapes. What does it mean to be emotionally laced by the poison of steel? While contemporary texts on the experience of environmental toxicity tend to waver between the material and semiotic/metaphorical as distinct poles, this essay proposes that we braid these oft-polarized terms through the work of ethnography. Through this dialogic process between aesthetics and anthropology, we encounter the ways in which artists have sought to understand ecological crises through a mobilization of the senses, which are crucial for understanding toxicity as it vacillates between visibility and invisibility.